2013
DOI: 10.1371/journal.pone.0070730
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Differentiation Persists after Male Gametogenesis in Natural Populations of the Perennial Herb Helleborus foetidus (Ranunculaceae)

Abstract: Despite the importance of assessing the stability of epigenetic variation in non-model organisms living in real-world scenarios, no studies have been conducted on the transgenerational persistence of epigenetic structure in wild plant populations. This gap in knowledge is hindering progress in the interpretation of natural epigenetic variation. By applying the methylation-sensitive amplified fragment length polymorphism (MSAP) technique to paired plant-pollen (i.e., sporophyte-male gametophyte) DNA samples, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 63 publications
8
47
0
1
Order By: Relevance
“…New epigenetic variants could have arisen spontaneously (e.g., via unfaithful meiotic transmission, leading to parent‐offspring differences; Herrera et al. 2013; Lauria et al. 2014) and/or in response to the environmental changes brought about by disturbance (e.g., somatic modifications between the seed and adult plant stages; Boyko and Kovalchuk 2008; Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…New epigenetic variants could have arisen spontaneously (e.g., via unfaithful meiotic transmission, leading to parent‐offspring differences; Herrera et al. 2013; Lauria et al. 2014) and/or in response to the environmental changes brought about by disturbance (e.g., somatic modifications between the seed and adult plant stages; Boyko and Kovalchuk 2008; Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from both animals and plants indicate that epigenetic resetting is not always complete and hence that acquired epigenetic states may be transmitted from parents to offspring ('germ-line epigenetic inheritance' or 'incomplete epigenetic resetting' or 'incomplete epigenetic reprogramming'; e.g. [6][7][8][9][10][11][12][13][14] reviewed in [4,5,[15][16][17][18][19]). …”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these epigenetic responses provide an adaptive advantage to offspring that are subjected to those same environmental conditions [46]. To fully address these questions, laboratory-based studies on model organisms should be coupled with natural and manipulative studies on natural populations and nonmodel organisms to obtain a clearer picture of how epigenetics affects organisms [38].…”
Section: Discussionmentioning
confidence: 99%
“…Both facilitated and pure tend to exhibit non-Mendelian segregation and both can be affected by stochasticity in addition to environmental conditions. Researchers have begun designing elegant studies that control for genetic differences among individuals [14,[37][38][39][40]. These studies have suggested that some epigenetic variation is correlated with environment and some environmentally induced epigenetic variation is passed on to the next generation.…”
Section: Measuring Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation